1) sin3a - sina / cos3a + cosa = tga
2sin(3a-a/2)*cos(3a+a/2) / 2cos(3a+a/2)*cos(3a-a/2) = tga
2sin(2a/2)*cos(4a/2) / 2cos(4a/2)*cos(2a/2) = tga
2sin(a)*cos(2a) / 2cos(2a)*cos(a) = tga
sin(a)/coa(a) = tga
2) Cos(a)-Cos(5a) / Sin(5a)+Sin(a)=tg(2a)
-2sin(a+5a/2)*sin(a-5a/2) / 2sin(5a+a/2)*cos(5a-a/2) = tg(2a)
-2sin(6a/2)*sin(-4a/2) / 2sin(6a/2)*cos(-4a/2) = tg(2a)
-2sin(3a)*sin(-2a) / 2sin(3a)*cos(-2a) = tg(2a)
-2sin(3a)*(-sin(2a)) / 2sin(3a)*cos(2a) = tg(2a)
2sin(3a)*sin(2a) / 2sin(3a)*cos(2a) = tg(2a)
sin(2a) / cos(2a) = tg(2a)
ОДЗ:
Возводим в квадрат:
Возводим в квадрат:
Замена переменной:
Обратная замена:
D=5
Оба корня входят в ОДЗ
О т в е т. cумма корней :![\frac{1+ \sqrt{5} }{2}+\frac{1- \sqrt{5} }{2}=1](/tpl/images/1360/4693/1f3aa.png)